Genome-wide characterization and expression profiling of HD-Zip gene family related to abiotic stress in cassava - Ding, Zehong (PLoS One, 2017)
Homeodomain-leucine zipper (HD-Zip) gene family plays important roles in various abiotic stresses and hormone signaling in plants. However, no information is currently available regarding this family in cassava (Manihot esculenta), an important drought-tolerant crop in tropical and sub-tropical areas. Here, 57 HD-Zip genes (MeHDZ01-57) were identified in the cassava genome, and they were classified into four subfamilies based on phylogenetic analysis, which was further supported by their gene structure and conserved motif characteristics. Of which five gene pairs were involved in segmental duplication but none for tandem duplication, suggesting that segmental duplication was the main cause for the expansion of MeHDZ gene family in cassava. Global expression profiles revealed that MeHDZ genes were constitutively expressed, or not expressed, or tissue-specific expressed in examined tissues in both cultivated and wild subspecies. Transcriptomic analysis of three genotypes showed that most of MeHDZ genes responded differently to drought and polyethylene glycol treatments. Subsequently, quantitative RT-PCR analysis revealed comprehensive responses of twelve selected MeHDZ genes to various stimuli including cold, salt, and ABA treatments. These findings will increase our understanding of HD-Zip gene family involved in abiotic stresses and signaling transduction, and will provide a solid base for further functional characterization of MeHDZ genes in cassava.